Pakistan Journal of Ophthalmology: A bibliometric review from 2018 – 1995 - Baladi, Zameer Hussain; satti, Mumtaz Hussain (Pakistan Journal of Ophthalmology, 2020)
Purpose: To measure the growth of research published in Pakistan Journal of Ophthalmology (PJO) during the year 2017 – 1995 through the bibliometric study. Study Design: Retrospective and observational study. Place and Duration of Study: Medical Libraries, College of Applied Medical Sciences and College of Science & Health Profession, King Saud bin Abdulaziz University for Health Sciences, Riyadh Saudi Arabia. June 2018 to April 2019. Material and Methods: The data for the study was retrieved from websites of e-journal of Pakistan Journal of Ophthalmology (PJO) and Pak Medi Net for statistical analysis in MS Excel 2010 version. Results: This study examined 855 articles published in 24; 35% volumes and 96; 8.9% articles per issues in Pakistan Journal of Ophthalmology (PJO) from 2018 to 1995 contributed by 2816; 3.2% authors. A gender-wise comparison among the contributing authors revealed male 2378 (84.4%) higher than the female 437 (15.5%) authors. It is also revealed that 141; 16.4% of articles were written by a female as the first author during the studied period. Majority of 734; 85.8% articles were written by multi-authors instead of solo authors 121; 14.1% out of 855 articles. Conclusion: This study finds that regularly publishing of Pakistan Journal of Ophthalmology (PJO) get the confidence of researchers, institutes, and readers. This journal follows the international rules for peer-review processes. This process assures authors and help journal to maintaining a constant approach as a strategy in publishing publications